Answer:
x = 7
y = 17
Explanation:
Substitution method:
y = 2x + 3 ---------------(I)
y = 3x - 4 ----------------(II)
Substitute y = 3x - 4 in equation (I)
3x - 4 = 2x + 3
Add 4 to both sides
3x = 2x + 3 + 4
3x = 2x + 7
Subtract '2x' from both sides
3x - 2x = 7
![\sf \boxed{\bf x = 7}](https://img.qammunity.org/2023/formulas/mathematics/college/2dhhqipzpd8g3ci9htujg6zmiil14gti0s.png)
Substitute x = 7 in any one of the equation, Here I substituting in equation (I)
y = 2x + 3
y = 2*7 + 3
= 14 + 3
![\sf \boxed{\bf y = 17}](https://img.qammunity.org/2023/formulas/mathematics/college/flq3mev5b5r0l282v4bqeytunkdl1ij7kn.png)